NAD(P)H:Quinone Oxidoreductase 1 (NQO1) Localizes to the Mitotic Spindle in Human Cells - Siegel, David (Public Library of Science, 2012)
NAD(P)H:quinone oxidoreductase 1 (NQO1) is an FAD containing quinone reductase that catalyzes the 2-electron reduction of a broad range of quinones. The 2-electron reduction of quinones to hydroquinones by NQO1 is believed to be a detoxification process since this reaction bypasses the formation of the highly reactive semiquinone. NQO1 is expressed at high levels in normal epithelium, endothelium and adipocytes as well as in many human solid tumors. In addition to its function as a quinone reductase NQO1 has been shown to reduce superoxide and regulate the 20 S proteasomal degradation of proteins including p53. Biochemical studies have indicated that NQO1 is primarily located in the cytosol, however, lower levels of NQO1 have also been found in the nucleus. In these studies we demonstrate using immunocytochemistry and confocal imaging that NQO1 was found associated with mitotic spindles in cells undergoing division. The association of NQO1 with the mitotic spindles was observed in many different human cell lines including nontransformed cells (astrocytes, HUVEC) immortalized cell lines (HBMEC, 16HBE) and cancer (pancreatic adenocarcinoma, BXPC3). Confocal analysis of double-labeling experiments demonstrated co-localization of NQO1with alpha-tubulin in mitotic spindles. In studies with BxPc-3 human pancreatic cancer cells the association of NQO1 with mitotic spindles appeared to be unchanged in the presence of NQO1 inhibitors ES936 or dicoumarol suggesting that NQO1 can associate with the mitotic spindle and still retain catalytic activity. Analysis of archival human squamous lung carcinoma tissue immunostained for NQO1 demonstrated positive staining for NQO1 in the spindles of mitotic cells. The purpose of this study is to demonstrate for the first time the association of the quinone reductase NQO1 with the mitotic spindle in human cells.